Overview of Therapy and Medication Adherence in Outpatient Post-Stroke Patients at RSUD Taman Husada Bontang - Fauzi, Lailla Affianti; Kushartanti, Wara; Arovah, Novita Intan (Jurnal FARMASIMED (JFM), 2025)
Background: Stroke is a cerebrovascular disease that can cause physical and cognitive impairments, including a high risk of depression. Medication adherence plays a crucial role in preventing complications and improving patients' quality of life. Objective: This study aims to describe the therapy and evaluate medication adherence among post-stroke outpatients in the recurrent and non-recurrent stroke groups at RSUD Taman Husada Kota Bontang. Methods: This study employs a cross-sectional design, involving a total of 152 patients, consisting of 119 non-recurrent stroke patients and 33 recurrent stroke patients. Data were collected through interviews, secondary data retrieval from medical records, and primary data obtained from the MMAS-8 (Morisky Medication Adherence Scale-8) questionnaire to assess medication adherence levels. Data were analyzed descriptively, and a chi-square test was performed to examine the association between medication adherence and stroke recurrence. Results: The findings indicate that both recurrent and non-recurrent stroke groups were prescribed antiplatelet, anticoagulant, neuroprotective, and antihypertensive drugs. Additionally, lower medication adherence was more frequently observed in recurrent stroke patients compared to non-recurrent stroke patients (24% vs. 26%). Analysis of the MMAS-8 questionnaire items revealed that forgetting to take medication occurred in both groups, but was more common among non-recurrent stroke patients (23% vs. 9%). Conclusion: This study highlights the need for continuous monitoring of therapy profiles and efforts to improve medication adherence to prevent further complications in post-stroke patients. The findings emphasize the importance of ongoing evaluation and innovative medication education for post-stroke patients.